Measuring the Impact of Dollarization on Economic Growth in Ecuador Using the ARDL Autoregressive Model for the Period (1970-2021) - Bazzaz, Najah Hawar Saeed; Ahmed, Salam Anwar (Research Parks Publishers, 2023)
The research aimed to know the impact of the policy of rotation on economic growth in Ecuador during the period (1970-2021) by adopting the autoregressive distributed lagi(ARDL) model. The independent variables in the model were dollarization, trade openness, investment, inflation, and net transfers from abroad. Like the dependent variable, economic growth is per capita GDP. One of the research's most notable conclusions is that dollarization had no appreciable effects on Ecuador's economic development, either in the short or long term, and the investment variable was the most influential in economic growth.